Effects of EDM Parameters on MRR & SR of automobile Chassis material by ANOVA - Deepak (Innovative Research Thoughts, 2017)
Electric Discharge Machining (EDM) is a unconventional machining process somewhere compound and complex shapes can be machined. Only electrically conductive materials can be machined by this method. It is accomplished of machining geometrically complex or hard materials, that are precise and difficult-to-machine such as heat treated tool steels, composites, super alloys, ceramics, carbides, heat resistant steels etc. To observe the all results EN31 heavy vehicle chassis and D3 steel heavy vehicle chassis with respect to weight, stiffness and strength .These materials are being widely used in die and mould making industries, aerospace, aeronautics and nuclear industries. In this work D3steel is the material used for the machining purpose and Copper is used as an electrode. It is essential to consider most number of input parameters to get the better result. In this process Taguchi approach is used to create L27 orthogonal matrix. Experiments were conducted with the L27 orthogonal array based on the Taguchi method. Moreover, the signal-to-noise ratios associated with the observed values in the experiments were determined. The purpose of ANOVA to see the individual effect of control factors on MRR and SR. In the present work, Optimization of MRR and SR on EDM conducted by using Taguchi and ANOVA.